EFEK INFUS MIDAZOLAM INTRAOPERATIF PADA VARIABILITAS TEKANAN DARAH DAN KEJADIAN HIPERTENSI INTRAOPERATIF PADA PASIEN HIPERTENSI - Rinta Ramadhani; Angelina Najoan; Nurul Azzah; Galang Ramadhan; Ratih Kusumadewi (PT. Hasba Edukasi Mandiri, 2025)
Background: Effective blood pressure control during surgery is crucial, especially for patients with hypertension, as blood pressure variability (BPV) and intraoperative hypertension (IOH) increase the risk of postoperative complications such as acute kidney injury (AKI). Midazolam is widely used for sedation, induction, and co-induction of anesthesia, but its effects on intraoperative hemodynamic stability particularly BPV and IOH in hypertensive patients are not fully understood. Objective: This scoping review summarizes current evidence on the effects of intraoperative midazolam infusion on BPV and IOH in hypertensive patients and identifies existing research gaps .Methods: A scoping review was conducted following PRISMA-ScR guidelines. Literature searches were performed in PubMed, Google Scholar, and ClinicalTrials for studies published between 2021 and 2025 with RCT, quasi-experimental, cohort, or observational designs reporting intraoperative hemodynamic parameters. Study quality was assessed using the MMAT 2018. Results: Ten studies met the inclusion criteria. Midazolam caused a milder blood pressure decrease than propofol but provided less hemodynamic stability than etomidate. Other agents, such as remimazolam and dexmedetomidine, often demonstrated superior hemodynamic profiles. Although midazolam can reduce stress responses and early blood pressure fluctuations, most studies did not evaluate BPV using comprehensive statistical methods. BPV and IOH were consistently associated with higher postoperative risks, particularly AKI in hypertensive patients.Conclusion: Intraoperative midazolam infusion may help maintain hemodynamic stability, but evidence regarding its effectiveness in reducing BPV and preventing IOH remains limited. Further randomized controlled trials are needed to directly assess the impact of midazolam infusion on BPV in hypertensive patients and compare it with other sedative agents.